Dentofacıal Effects Of Maxıllary Sagıttal Applıance - Ayhan Enacar; Mehmet Özgen; Murat Demirhanoğlu (Galenos Yayinevi, 1993)
Y-plate or sagittal appliance has been widely used in our clinic in patients who portray maxillary arch deficiency associated with class III tendency in order to regain the required space particularly for the accomodation of upper cuspids. This study is carried out on initial and final cephalograms of 16 cases who were utilized with maxillary sagittal appliance. The skeletal, dental, and soft tissue profile cephalometric evaluation indicated statistically significant upper molar distalization and concurrent labialization of upper incisors.